THE IMPACT OF SOCIAL INFLUENCE, HEDONIC MOTIVATION AND HABIT ON USERS’ INTENTION TO CONTINUE USING NETFLIX (CASE STUDY OF GEN-Z CONSUMERS IN MANADO) - Elisabeth Pangkey; James Massie; Ferdinand Tumewu (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2023)
This study aims to determine the influence of Social Influence, Hedonic Motivation and Habit towards Users’ Intention to Continue Using Netflix in Manado. Data analysis methods used is Multiple Regression Analysis. The sample in this research are Generation-Z Netflix users in Manado. This research requires around 90 Respondents. Sampling in this study uses by Purposive Sampling technique. The results are (1) Social Influence affects Users’ Intention to Continue Using Netflix among Generation-Z in Manado. (2) Hedonic Motivation affects Users’ Intention to Continue Using Netflix among Generation-Z in Manado. (3) Habit affects Users’ Intention to Continue Using Netflix among Generation-Z in Manado, and (4) Social Influence, Hedonic Motivation and Habit affects Users’ Intention to Continue Using Netflix among Generation-Z in Manado. Keywords: social influence, hedonic motivation, habit, users’ intention to continue